2023
DOI: 10.1002/ase.2261
|View full text |Cite
|
Sign up to set email alerts
|

Initial impressions of ChatGPT for anatomy education

Abstract: The release of Open AI's ChatGPT (Generative Pre-trained Transformer) in November 2022 has generated widespread attention and speculations in the world's mainstream media, social media, and tech industries. 1 It can perform text production, translation, and even answer questions based on the input it receives. 2 For instance, it can produce well-organized essays, poetry, and computer programs. In a recent white paper by the University of Pennsylvania's Wharton School of Business, the ChatGPT chatbot scored hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…ChatGPT has been explored as a tool for medical education, particularly in enhancing learning, interpretation, and recall of medical information [ 11 , 12 ]. Some studies have shown that ChatGPT can provide reliable information comparable to medical students in specific medical fields such as parasitology.…”
Section: Reviewmentioning
confidence: 99%
“…ChatGPT has been explored as a tool for medical education, particularly in enhancing learning, interpretation, and recall of medical information [ 11 , 12 ]. Some studies have shown that ChatGPT can provide reliable information comparable to medical students in specific medical fields such as parasitology.…”
Section: Reviewmentioning
confidence: 99%
“…For example, ChatGPT could grade written assignments and provide constructive suggestions for improving writing and speaking (van Dis et al, 2023). Additionally, ChatGPT could provide personalized learning for a large number of students anytime and anywhere (Mogali, 2023). Nevertheless, there is a notable paucity of empirical research focusing specifically on the use of ChatGPT in education.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, health care professionals could potentially benefit, especially from GPT-4's conclusive and often nonobvious insights to multiple-choice questions, as these users have the ability to verify crucial details [13,14,41]. For instance, there is potential for using GPT-3.5 and GPT-4 in a medical education tutoring environment, as evidenced by its successful application in anatomy [47]. However, when using either GPT-3.5 or GPT-4 for medical applications, its differing accuracy across specialties must also be taken into account [48].…”
Section: Principal Findingsmentioning
confidence: 99%